Consumption of aquatic products and meats in Chinese residents: A nationwide survey - Wang, Qihe; Liu, Sana; Wang, Huijun; Su, Chang; Liu, Aidong; Jiang, Liying (Frontiers in Nutrition, 2022)
Objective: To provide the most recent national estimates for the consumption of aquatic products and meats among Chinese residents. Methods: This study was conducted in 14 provinces of China, using a multi-stage stratified random cluster sampling method and a population-proportional sampling procedure. Aquatic products and meats consumption was measured by a 3-day, 24-hour dietary recall. Chinese residents aged three years and above (n = 24,106) completed a face-to-face dietary interview. Results: The average daily consumption of meat and aquatic products for the all-aged population was 70.9 g and 48.0 g, respectively, which aligned with Dietary Guidelines (40-75g/d) for Chinese Residents (2016). On the one hand, intake of aquatic products among Chinese people was relatively insufficient, especially for adolescents and elder people (<40g/d). On the other hand, males, mainly aged 19-60, generally consumed too much meat (>80g/d), and 19-44 grouping consumed more than 70g/d of red meat. Besides, urban residents and individuals with higher socioeconomic status (SES) have exhibited comprehensively healthy dietary preferences than rural ones and those with a lower SES do. Women and the higher SES group tend to be closer to the dietary guidelines for the Chinese. Conclusions: The consumption of meat and aquatic products varied with age, gender, region and SES. Detecting patterns in consumption is particularly relevant for policy makers, researchers and health professionals in the formulation of dietary recommendations and estimating potential health outcomes.